Single-Nucleotide RNA Maps for the Two Major Nosocomial Pathogens Enterococcus faecalis and Enterococcus faecium - Michaux, Charlotte; Hansen, Elisabeth E.; Jenniches, Laura; Gerovac, Milan; Barquist, Lars; Vogel, Jörg (Frontiers in Cellular and Infection Microbiology, 2020)
Enterococcus faecalis and faecium are two major representative clinical strains of the Enterococcus genus and are sadly notorious to be part of the top agents responsible of nosocomial infections. Despite their critical implication in worldwide public healthcare, essential and available resources such as deep transcriptome annotations remain poor, which also limits our understanding post-transcriptional control small regulatory RNA (sRNA) functions in these bacteria. Here, using the dRNA-seq technique in combination with ANNOgesic analysis, we successfully mapped and annotated transcription start sites (TSS) of both E. faecalis V583 and E. faecium AUS0004 at single nucleotide resolution. Analyzing bacteria in late exponential phase, we capture ~40% (E. faecalis) and 43% (E. faecium) of the annotated protein-coding genes, determine 5’ and 3’ UTR (untranslated region) length, and detect instances of leaderless mRNAs. The transcriptome maps revealed sRNA candidates in both bacteria, some found in previous studies and new ones. Expression of candidate sRNAs is being confirmed under biologically relevant environmental conditions. This comprehensive global TSS mapping atlas provides a valuable resource for RNA biology and gene expression analysis in the Enterococci. It can be accessed online at www.helmholtz-hiri.de/en/datasets/enterococcus through an instance of the genomic viewer JBrowse.